Global governance through transnational network organizations: The scope and limitations of civil society self-organization - Kristine Kern (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2004)
When the topic of global governance or post-national governance arises, it generally does so in the context of the co-operation between nation states, international agreements and the role of international organizations. As opposed to this, global governance through the self-organization of transnational civil society is rarely discussed. Therefore, the aim of this paper is to demonstrate the scope and limitations of global governance through civil society self-organization. The case of the “Forest Stewardship Council” (FSC), which is now deemed a success, has been selected to demonstrate this phenomenon at work. What is involved here is a globally distributed environmental label for the certification of sustainably managed forests. The FSC shows how a private civil society regime can be implemented, how its implementation can be controlled and how violations can be sanctioned. It may be stated that the case of the Forest Stewardship Council is a form of global governance without nation-state involvement that can be viewed as a complete alternative to global governance through nation states. – – Wenn von globaler Governance oder postnationalem Regieren die Rede ist, geht es zumeist um die Kooperation von Nationalstaaten im Rahmen internationaler Vereinbarungen oder um die Rolle internationaler Organisationen. Im Gegensatz dazu wird globale Governance durch die Selbstorganisation transnationaler Zivilgesellschaften selten thematisiert. Aus diesem Grunde will der vorliegende Beitrag die Möglichkeiten und Grenzen globaler Governance durch zivilgesellschaftliche Selbstorganisation aufzeigen. Ausgewählt wurde ein Fall, der mittlerweile als Erfolg gilt: das ,,Forest Stewardship Council“ (FSC). Dabei handelt es sich um ein weltweit vergebenes Umweltzeichen für die Zertifizierung nachhaltig bewirtschafteter Wälder. Der Fall des FSC zeigt, wie ein nichtstaatliches Regelwerk implementiert und seine Umsetzung kontrolliert werden kann und wie Verstöße sanktioniert werden können. Bei dem hier analysierten Fall des Forest Stewardship Council handelt es sich um eine Form der globalen Governance ohne Nationalstaat, die durchaus als eine Alternative zur globalen Governance durch Nationalstaaten gesehen werden kann.
Keywords: 300